2021
DOI: 10.1371/journal.pone.0253037
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of transcriptomic profiles of Huntington’s disease patients

Abstract: Description of robust transcriptomic alterations in Huntington’s disease is essential to identify targets for biochemical studies and drug development. We analysed publicly available transcriptome data from the brain and blood of 220 HD patients and 241 healthy controls and identified 737 and 661 genes with robustly altered mRNA levels in the brain and blood of HD patients, respectively. In the brain, a subnetwork of 320 genes strongly correlated with HD and was enriched in transport-related genes. Bioinformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Position-Specific Iterated BLAST (PSI-BLAST) analysis of Bdwf protein sequence revealed that Bdwf shares sequence similarities with MSANTD4 and Zbed4 in mouse and ZBED4 in humans. While MSANTD4 has been linked to Huntington’s disease, and recent studies have linked ZBED4 to schizophrenia and Phelan-McDermid syndrome, little is known about the underlying mechanism of these proteins (Nyegaard et al ., 2010; Mitz et al ., 2018; Schenkel et al ., 2021; Seefelder and Kochanek, 2021). Our study may provide new and valuable entry-points for further research on the role of these proteins in the nervous system function and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Position-Specific Iterated BLAST (PSI-BLAST) analysis of Bdwf protein sequence revealed that Bdwf shares sequence similarities with MSANTD4 and Zbed4 in mouse and ZBED4 in humans. While MSANTD4 has been linked to Huntington’s disease, and recent studies have linked ZBED4 to schizophrenia and Phelan-McDermid syndrome, little is known about the underlying mechanism of these proteins (Nyegaard et al ., 2010; Mitz et al ., 2018; Schenkel et al ., 2021; Seefelder and Kochanek, 2021). Our study may provide new and valuable entry-points for further research on the role of these proteins in the nervous system function and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 Based on these findings, the CDC42 dysregulation and its clinical value in serving as a biomarker for the neurodegenerative disease have been explored in recent studies. 27 , 28 , 29 , 30 For, instance, one study exhibits that the CDC42 is overexpressed in Huntington's disease patients. 27 Another study discloses that CDC42 serves as a differentially expressed RNA in AD patients by bioinformatics analysis from the GSE48350 data.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 , 29 , 30 For, instance, one study exhibits that the CDC42 is overexpressed in Huntington's disease patients. 27 Another study discloses that CDC42 serves as a differentially expressed RNA in AD patients by bioinformatics analysis from the GSE48350 data. 28 However, the study about detecting CDC42 expression in AD patients is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA metabolism dysregulation is a common feature of most neurodegenerative diseases [ 51 ]. Accordingly, dysregulated gene expression in HD patients’ brain samples or in in vivo and in in vitro models, has been described, exploiting different genome-wide techniques [ 52 , 53 , 54 , 55 , 56 , 57 ]. Alteration in RNA expression and processing might be identifiable from the very early stages of the disease, when neurons might be still viable, although not properly functional.…”
Section: Rna: a New Potential Class Of Biomarkersmentioning
confidence: 99%